2020
DOI: 10.7454/jki.v23i3.1090
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions toward Considering Nursing as A Career Choice among Secondary School Students

Abstract: Demand for a nursing career in Malaysia has increased, although it has not been a popular course of choice among students. Understanding the perceptions of students about nursing may help identify any misconception toward the profession and their consideration to choose nursing as a career. This study aimed to identify the perceptions of secondary school students about nursing and their potential interest in joining a nursing career. A cross-sectional study using convenience sampling was conducted among 155 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Present study revealed that more than half (52.3%) students had good perception towards male enrolment in nursing which is consistent with the finding of the study conducted in Nigeria which revealed that more than half (53%) senior secondary students held a positive perception towards nursing as a career choice for men. 26 Similarly, (Hasan, 2020) gave a contradictory view that stigma of nursing profession is suitable only for women and men are not favourable in considering nursing as their career choice. 14 On the other hand, present study resonates with the finding of study which reported no significant association between perception of male enrolment with various sociodemographic variables 26 whereas, inconsistent finding conducted in Nigeria revealed the significant association between male and female attitudes towards nursing as a career for men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Present study revealed that more than half (52.3%) students had good perception towards male enrolment in nursing which is consistent with the finding of the study conducted in Nigeria which revealed that more than half (53%) senior secondary students held a positive perception towards nursing as a career choice for men. 26 Similarly, (Hasan, 2020) gave a contradictory view that stigma of nursing profession is suitable only for women and men are not favourable in considering nursing as their career choice. 14 On the other hand, present study resonates with the finding of study which reported no significant association between perception of male enrolment with various sociodemographic variables 26 whereas, inconsistent finding conducted in Nigeria revealed the significant association between male and female attitudes towards nursing as a career for men.…”
Section: Discussionmentioning
confidence: 99%
“…11 However, perceiving the importance of recruiting male nurse, Nepal nursing council has issued notice regarding the inclusion of 15% of male students in June 2018 12 and estimating 1000 male nurse graduates by 2021. 13 Perception is highly subjective and usually not based on the facts that greatly influence choosing nursing as a career especially among younger generation. It could be a well-planned strategy to change the perception of high school students towards nursing and its career perspectives.…”
Section: Introductionmentioning
confidence: 99%